New Plants for Florida: Tropical Foliage - Jake Henny; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS, 2003)
Foliage breeding began in 1976 at FAES with Jake Henny and Gary Wilfret focusing on members of the family Araceae (referred to as aroids) and Caladium, respectively. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.